The Role of Commuting Stress on Job Satisfaction: Burnout as Mediator - Kristiyanto, Andreas Ari; Suyasa, P. Tommy Y. S. (UI Scholars Hub, 2026)
Abstract This study examines the role of commuting stress on job satisfaction, with burnout as a mediating variable. Data were collected from 113 commuting employees in urban areas, primarily within Greater Jakarta, an area known for severe traffic congestion, using a quantitative approach. Participants completed three validated questionnaires: the Minnesota Satisfaction Questionnaire (MSQ) for job satisfaction, the Multimodal Commuting Stress Scale (MCSS) for commuting stress, and the Maslach Burnout Inventory (MBI) for burnout. Data were analyzed using SEM-PLS and processed using SmartPLS 4.0. The results indicate that CS has a direct negative effect on job satisfaction and is positively associated with burnout, which subsequently reduces job satisfaction. These findings confirm that burnout partially mediates the relationship between CS and job satisfaction. This study has practical implications for urban planning and organizational policy, emphasizing the need to consider commuting conditions as a key factor affecting employee wellbeing and productivity. By using a multidimensional scale to measure commuting stress, this research strengthens the understanding of psychological mechanisms linking commuting challenges to workplace outcomes.